A REVIEW ON BIOLOGICAL ACTIVITIES OF COMMON MALLOW (Malva sylvestris L.) - Paul, Dipak (Innovare Journal of Life Sciences, 2016)
Since time immemorial, medicinal plants have been used by various communities to cure a large number of ailments. Research in medicinal plants has received a renewed focus in recent years. Plant based system of medicine being natural does not pose any serious complications. Phytochemical compounds in plants are known to be biologically active aiding. Malva sylvestris L. (Malvaceae) is a medicinal plant usually known as common mallow. The purpose of this article is to review information available in scientific literature on the biological activities of the plant. Malva sylvestris having a strong antioxidant, anti-inflammatory, anticancer, wound healing, hepatoprotective, antinociceptive and antimicrobial activities are reviewed in this article. It is evident from current literature that Malva sylvestris is one of the most promising medicinal plant species. However, extensive research in the area of isolation and characterization of the active compounds of Malva sylvestris is essential so that better, safer and cost effective drugs for curing various diseases and infections can be developed.